Organic association molecule / polyetherimide energy storage composite dielectric film and preparation method and application thereof

The preparation of energy storage composite dielectric films by composited organic associative molecules with polyetherimides has solved the problems of low energy storage efficiency and poor reliability in the prior art, and achieved high energy storage density and good reliability under high electric field and high temperature sex.

CN119410145AActive Publication Date: 2025-02-11HARBIN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411529684.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing polyetherimide-based energy storage composite media perform poorly in high electric field, high temperature, and complex electric and thermal coupling environments, resulting in low energy storage efficiency and poor reliability of pulse capacitors.

Method used

The energy storage composite dielectric film is prepared by combining organic associative molecules with polyetherimide. The organic small molecules repelling and electron-philic properties are formed by non-covalent bonds to form molecular associative fillers to enhance the insulating characteristics and energy storage density of the medium. .

Benefits of technology

Under the conditions of 150℃ and 660kV/mm, the charge and discharge efficiency reached 91%, and the energy storage density reached 6.52J/cm3, which significantly improved the service reliability and short-term breakdown performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410145A_ABST
    Figure CN119410145A_ABST
Patent Text Reader

Abstract

The invention discloses an organic association molecule / polyetherimide energy storage composite dielectric film as well as a preparation method and application thereof, and belongs to an energy storage dielectric material as well as a preparation method and application thereof. The invention aims to solve the problems of poor insulation property, high conductivity loss and low energy storage density of the existing polyetherimide-based energy storage composite medium. The invention relates to an organic association molecule / polyetherimide energy storage composite dielectric film which is formed by compounding organic association molecules and polyetherimide, the organic association molecule is formed by associating an electron-repelling small organic molecule and an electrophilic small organic molecule through a non-covalent bond; the organic molecule associated filler has strong intermolecular acting force, and can form more delocalized structures, thereby enhancing the electron capture effect and avoiding charge accumulation through strong scattering effect. The organic association molecule / polyetherimide energy storage composite dielectric film is used as an energy storage material of a pulse capacitor or used for a pulse energy storage device under the condition of electrothermal field coupling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to energy storage dielectric materials and a preparation method and application thereof. Background Art

[0002] At present, with the rapid expansion of high-end fields such as new energy vehicles, electromagnetic launch, and aerospace exploration, the demand for pulse capacitors has surged. These application scenarios place extremely high demands on capacitors, requiring not only higher voltage resistance, low dielectric loss, and high power density, but also energy storage stability and reliability in long-term use. However, existing energy storage materials perform poorly in high electric fields, high temperatures, and complex electrothermal coupling environments, becoming a bottleneck limiting the widespread application of pulse capacitors.

[0003] Polyetherimide (PEI) has attracted attention as a potential material to replace traditional biaxially oriented polypropylene due to its excellent temperature resistance, but its benzene ring structure easily promotes electron transport and reduces the energy storage efficiency of the material. To this end, researchers have proposed modification strategies including nanofiller doping, multilayer structure design and polymer blending, aiming to suppress carrier transport by forming localized states. However, these methods have limited improvement effects and are prone to accumulate space charges inside the dielectric, causing electric field distortion under complex electrothermal coupling conditions, further limiting performance improvements. Therefore, in order to develop dielectric materials with high electrical strength and excellent energy storage efficiency, it is urgent to start from reducing carrier accumulation and transmission, and to collaboratively design new material structures to meet the use requirements of pulse capacitors under harsh conditions. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of poor insulation properties, high conductivity loss and low energy storage density of existing polyetherimide-based energy storage composite dielectrics, and to provide an organic associated molecule / polyetherimide energy storage composite dielectric film and its preparation method and application.

[0005] An organic associating molecule / polyetherimide energy storage composite medium film is composited by an organic associating molecule and polyetherimide; the organic associating molecule is formed by the association of an organic small molecule with electron-repelling properties and an organic small molecule with electrophilic properties through non-covalent bonds;

[0006] The electron-repelling organic small molecule is 4-(dimethylamino)phenylboronic acid;

[0007] The electrophilic organic small molecule is tetrafluorotetracyanoquinolinodimethane, 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] or 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester.

[0008] A method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film is specifically completed by the following steps:

[0009] 1. dissolving the electron-repelling organic small molecules and the electrophilic organic small molecules in an organic solvent, and then ultrasonically treating for a period of time to obtain an associated molecular solution;

[0010] 2. dissolving polyetherimide into the associating molecule solution, and then performing vacuum defoaming treatment to obtain a bubble-free polyetherimide / associating molecule mixed solution;

[0011] 3. Scrape the bubble-free polyetherimide / associated molecule mixed solution on the substrate, and then dry it to obtain an organic associative molecule / polyetherimide energy storage composite medium film.

[0012] An organic associative molecule / polyetherimide energy storage composite dielectric film is used as an energy storage material for a pulse capacitor; the pulse capacitor is used in the field of electric-thermal field coupling of new energy vehicle inverters, electromagnetic emission pulse systems or aerospace exploration energy storage systems.

[0013] An organic associative molecule / polyetherimide energy storage composite dielectric film is used in a pulse energy storage device under electrothermal field coupling conditions. The pulse energy storage device can achieve an energy storage density of 6.52 J / cm at 150°C, 660 kV / mm, and a charge and discharge efficiency of 91%. 3 .

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. In the present invention, organic small molecules with opposite electron affinities are mixed in different proportions to construct a composite material (molecular association filler) interacting through non-covalent bonds, and the composite material is added into polyetherimide (PEI) to prepare a composite dielectric; the electron-repelling filler (organic small molecule with electron-repelling properties) is selected from 4-(dimethylamino)phenylboronic acid (4-NB), and the electron-attracting filler (organic small molecule with electrophilic properties) is selected from tetrafluorotetracyanoquinolinodimethane (F4TCNQ), 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2, 1(3H)-dimethoxy)]]bis[propylamine] (ITIC) or 2ALPHA-phenyl-1,2(2ALPHA)-high[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester (PCBM); molecular association filler, strong intermolecular force, can form more delocalized structures, which not only enhances the electron capture effect, but also avoids the accumulation of charge through strong scattering effect, and can also reduce the free volume of the composite medium, and finally effectively regulates the transport behavior of carriers and reduces the conductivity loss; and the presence of molecular association filler makes the electric dipole layer formed at the electrode and the interface, which plays a role in hindering electron injection; the results show that the energy storage density of the prepared composite medium reaches 6.52J / cm at 150℃, 660kV / mm, and the charge and discharge efficiency is 91%. 3 ;

[0016] Second, the organic associated molecule / polyetherimide energy storage composite dielectric film prepared by the present invention can form an electric dipole layer at the electrode and the interface by using the molecular associated filler, change the interface potential distribution, and play a role in hindering electron injection;

[0017] 3. The organic associative molecule / polyetherimide energy storage composite dielectric film prepared by the present invention can utilize the delocalized structural oscillation of the molecular associative filler to dissipate the energy of electrons, reduce the electron jump conduction distance, and hinder the long-distance transmission of electrons;

[0018] Fourth, the organic associating molecule / polyetherimide energy storage composite dielectric film prepared by the present invention can utilize the strong dipole-dipole effect of the associating molecules composed of the organic small molecules with attractive electronic properties and the organic small molecules with repelling electronic properties to enhance the dipole moment in the dielectric, thereby improving the relative dielectric constant of the dielectric;

[0019] 5. The present invention enhances the intermolecular forces of the material by introducing molecular association fillers, making it have strong impact resistance, and can effectively resist the large current impact generated by the pulse capacitor, and prevent the damage of the thin film material caused by the electron migration caused by the large current impact, thereby significantly improving the service reliability of the material. At the same time, the invention improves the short-time breakdown performance of the composite medium while reducing the introduction of deep traps, and the low trap density scheme also shows good application potential in the long-term durability of the capacitor film. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD patterns of organic associating molecules / polyetherimide energy storage composite dielectric films prepared in different embodiments;

[0021] Figure 2 Infrared spectra of organic associating molecules / polyetherimide energy storage composite dielectric films prepared in different embodiments;

[0022] Figure 3 1 is a curve diagram of the dielectric constant and dielectric loss of the composite dielectric film at 150°C as a function of frequency, wherein (a) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (b) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; (c) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associating molecules;

[0023] Figure 4: is a Weibull distribution diagram of the breakdown field strength of the composite dielectric film at 150°C; in the figure (a) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (b) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; (c) is an organic associative molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with indene-2,1(3H)-dimethylene)]]bis[propylamine] associative molecule; (d) is a pure polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associative molecule in Examples 11 to 15; (d) is a polyetherimide energy storage composite dielectric film doped with tetrafluorotetracyanoquinolinodimethane and a polyetherimide energy storage composite dielectric film obtained in Comparative Examples 1 to 2;

[0024] Figure 5 The intermolecular force simulation diagram of the associated molecules composed of different types of electrophilic small molecules / electron repelling small molecules according to different proportions in Examples 1 to 15;

[0025] Figure 6 The free volume simulation diagram of the organic associating molecule / polyetherimide energy storage composite dielectric film prepared in Examples 1 to 15;

[0026] Figure 7 The surface electrostatic potential cloud diagram and potential statistics diagram of the associated molecules. In the figure, (a) is the associated molecule of 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane; (b) is the associated molecule of 4-(dimethylamino)phenylboronic acid / 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1, 2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] associated molecule; (c) is 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associated molecule;

[0027] Figure 8The energy storage density diagram and energy storage efficiency diagram of the composite dielectric film at 150°C are shown in Figures 1 to 5; (a) and (b) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (c) and (d) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; :5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] associating molecules doped with polyetherimide to obtain an organic associating molecule / polyetherimide energy storage composite dielectric film; (e) and (f) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associating molecules in Examples 11 to 15;

[0028] Fig. 9 The energy storage density diagram and energy storage efficiency diagram of the pure polyetherimide energy storage dielectric film and the polyetherimide energy storage composite dielectric film doped with tetrafluorotetracyanoquinolinodimethane obtained in Comparative Examples 1 to 2 at 150° C.;

[0029] Fig.10 Figures 1 and 2 are the hopping conduction fitting diagram and the Schottky barrier fitting diagram of the composite dielectric film. In the figure, (a) and (b) are the organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (c) and (d) are the organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; (e) and (f) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associating molecules in Examples 11 to 15. DETAILED DESCRIPTION

[0030] Specific implementation method 1: This implementation method is an organic associating molecule / polyetherimide energy storage composite dielectric film, which is composed of an organic associating molecule and polyetherimide; the organic associating molecule is composed of an organic small molecule with electron-repelling properties and an organic small molecule with electrophilic properties that are associated through non-covalent bonds;

[0031] The electron-repelling organic small molecule is 4-(dimethylamino)phenylboronic acid;

[0032] The electrophilic organic small molecule is tetrafluorotetracyanoquinolinodimethane, 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] or 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester.

[0033] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the volume ratio of the organic associating molecule to the polyetherimide is 0.007:1. The other steps are the same as those of specific embodiment 1.

[0034] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the volume ratio of the electrophilic organic small molecule to the electron-repelling organic small molecule is 1:(0.3-3). The other steps are the same as those of specific implementation method 1 or 2.

[0035] Specific embodiment 4: This embodiment is a method for preparing an organic associating molecule / polyetherimide energy storage composite medium film, which is specifically completed by the following steps:

[0036] 1. dissolving the electron-repelling organic small molecules and the electrophilic organic small molecules in an organic solvent, and then ultrasonically treating for a period of time to obtain an associated molecular solution;

[0037] 2. dissolving polyetherimide into the associating molecule solution, and then performing vacuum defoaming treatment to obtain a bubble-free polyetherimide / associating molecule mixed solution;

[0038] 3. Scrape the bubble-free polyetherimide / associated molecule mixed solution on the substrate, and then dry it to obtain an organic associative molecule / polyetherimide energy storage composite medium film.

[0039] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the organic solvent described in step 1 is N-methylpyrrolidone, dimethylacetamide or N,N-dimethylformamide; the volume ratio of the total mass of the electron-repelling organic small molecules and the electrophilic organic small molecules described in step 1 to the organic solvent is (0.00105g-0.00126g): 1mL; the volume ratio of the total mass of the electron-repelling organic small molecules, the electrophilic organic small molecules and the polyetherimide described in step 2 to the organic solvent is (0.15g-0.18g): 1mL. The other steps are the same as specific embodiments 1 to 4.

[0040] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: in step 1, the electron-repelling organic small molecules and the electrophilic organic small molecules are dissolved in an organic solvent at 60°C to 70°C and a stirring speed of 300r / min to 500r / min; the ultrasonic treatment described in step 1 is carried out by using a gradient ultrasonic dispersion treatment combined with a gradient cooling technology, and the specific method is: first, the solution is ultrasonically dispersed for 30 minutes at a power of 200W and a temperature of 30°C, then the power is increased to 400W, the temperature is reduced to 25°C, and the solution is ultrasonically dispersed for 15 minutes at a power of 400W and a temperature of 25°C, and finally the power is increased to 500W, the temperature is reduced to 20°C, and the solution is ultrasonically dispersed for 10 minutes at a power of 500W and a temperature of 20°C. The other steps are the same as those of specific embodiments 1 to 5.

[0041] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 2, polyetherimide is dissolved in the associating molecule solution at 60°C to 70°C and a stirring speed of 300r / min to 500r / min; the vacuum defoaming treatment method described in step 2 is a gradient vacuum and gradient temperature treatment, specifically: first, stand for 5min to 15min in a vacuum environment of 500mbar and 60°C, then stand for 5min to 15min in a vacuum environment of 100mbar and 65°C, and finally stand for 5min to 15min in a vacuum environment of 10mbar and 70°C. The other steps are the same as those of specific embodiments 1 to 6.

[0042] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the drying method described in step three is:

[0043] ①. In an environment without natural light and with a relative humidity of 40%, keep warm at 70℃ for 4 hours and then keep warm at 120℃ for 2 hours;

[0044] ② In an environment without natural light and with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0045] ③. In an environment without natural light and with a relative humidity of 20%, keep warm for 4 hours at 200°C in an argon atmosphere;

[0046] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction;

[0047] The thickness of the organic associating molecule / polyetherimide energy storage composite medium film described in step 3 is 3 μm to 15 μm. The other steps are the same as those of specific embodiments 1 to 7.

[0048] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that an organic associative molecule / polyetherimide energy storage composite dielectric film is used as an energy storage material of a pulse capacitor; the pulse capacitor is used in the field of electric-thermal field coupling of new energy vehicle inverters, electromagnetic emission pulse systems or space exploration energy storage systems. The other steps are the same as specific embodiments 1 to 8.

[0049] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that an organic associating molecule / polyetherimide energy storage composite dielectric film is used for a pulse energy storage device under electrothermal field coupling conditions, and the pulse energy storage device can achieve an energy storage density of 6.52 J / cm at 150°C, 660 kV / mm, and a charge and discharge efficiency of 91%. 3 The other steps are the same as those in Specific Embodiments 1 to 9.

[0050] The following examples are used to verify the beneficial effects of the present invention:

[0051] Example 1: A method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules is specifically completed by the following steps:

[0052] 1. Under the conditions of 60° C. and a stirring speed of 300 r / min, an electron-repelling organic small molecule and an electrophilic organic small molecule are dissolved in N-methylpyrrolidone, and then ultrasonically treated for a period of time to obtain a 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associated molecular solution (F4TCNQ / 4-NB associated molecular solution);

[0053] The electron-repelling organic small molecule described in step 1 is 4-(dimethylamino)phenylboronic acid;

[0054] The electrophilic organic small molecule described in step 1 is tetrafluorotetracyanoquinodimethane (F4TCNQ);

[0055] The volume ratio of tetrafluorotetracyanoquinolinodimethane to 4-(dimethylamino)phenylboronic acid in step 1 is 1:1;

[0056] The volume ratio of the total mass of tetrafluorotetracyanoquinolinodimethane and 4-(dimethylamino)phenylboronic acid to N-methylpyrrolidone described in step 1 is 0.00126 g:1 mL;

[0057] 2. At 60℃ and stirring speed of 300r / min, PolyK Ultem 1000% polyetherimide is dissolved in 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinoline dimethane associated molecule solution, and then vacuum degassing is performed to obtain a bubble-free polyetherimide / associated molecule mixed solution;

[0058] The volume ratio of the total mass of the electron-repelling organic small molecule, the electrophilic organic small molecule and the polyetherimide described in step 2 to the organic solvent is 0.16 g:1 mL;

[0059] 3. Pour the bubble-free polyetherimide / associated molecule mixed solution evenly on a clean flat glass plate at a temperature of 70°C, raise the coating knife to a height of 15 μm, scrape horizontally at a speed of 5 cm / s, and then dry to obtain a 10 μm thick and densely structured organic associative molecule / polyetherimide energy storage composite medium film (denoted as FN 1-1);

[0060] The ultrasonic treatment described in step 1 is carried out by using a gradient ultrasonic dispersion treatment combined with a gradient cooling technology, and the specific method is: first, the solution is ultrasonically dispersed for 30 minutes at a power of 200W and a temperature of 30°C, then the power is increased to 400W, the temperature is reduced to 25°C, and the ultrasonic dispersion is carried out for 15 minutes at a power of 400W and a temperature of 25°C, and finally the power is increased to 500W, the temperature is reduced to 20°C, and the ultrasonic dispersion is carried out for 10 minutes at a power of 500W and a temperature of 20°C;

[0061] The vacuum degassing treatment method described in step 2 is to use a gradient vacuum and gradient temperature treatment, specifically: first, stand for 15 minutes in a vacuum environment of 500 mbar and 60°C, then stand for 15 minutes in a vacuum environment of 100 mbar and 65°C, and finally stand for 15 minutes in a vacuum environment of 10 mbar and 70°C;

[0062] The drying method described in step 3 is:

[0063] ①. In an environment without natural light and with a relative humidity of 40%, keep warm at 70℃ for 4 hours and then keep warm at 120℃ for 2 hours;

[0064] ② In an environment without natural light and with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0065] ③. In an environment without natural light and with a relative humidity of 20%, keep warm for 4 hours at 200°C in an argon atmosphere;

[0066] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0067] Example 2: The difference between this example and Example 1 is that the volume ratio of tetrafluorotetracyanoquinoline dimethane to 4-(dimethylamino)phenylboronic acid in step 1 is 1:2; the prepared 10 μm thick and dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as FN 1-2. The other steps and parameters are the same as those in Example 1.

[0068] Example 3: The difference between this example and Example 1 is that the volume ratio of tetrafluorotetracyanoquinoline dimethane to 4-(dimethylamino)phenylboronic acid in step 1 is 1:3; the prepared 10 μm thick and dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as FN 1-3. The other steps and parameters are the same as those in Example 1.

[0069] Example 4: The difference between this example and Example 1 is that the volume ratio of tetrafluorotetracyanoquinoline dimethane to 4-(dimethylamino)phenylboronic acid in step 1 is 2:1; the prepared 10 μm thick and dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as FN 2-1. The other steps and parameters are the same as those in Example 1.

[0070] Example 5: The difference between this example and Example 1 is that the volume ratio of tetrafluorotetracyanoquinoline dimethane to 4-(dimethylamino)phenylboronic acid in step 1 is 3:1; the prepared 10 μm thick and dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as FN 3-1. The other steps and parameters are the same as those in Example 1.

[0071] Example 6: A method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] associating molecules, which is specifically completed in the following steps:

[0072] 1. Under the conditions of 60° C. and a stirring speed of 300 r / min, the electron-repelling organic small molecules and the electrophilic organic small molecules are dissolved in N-methylpyrrolidone, and then ultrasonically treated for a period of time to obtain an associated molecular solution (ITIC / 4-NB associated molecular solution);

[0073] The electron-repelling organic small molecule described in step 1 is 4-(dimethylamino)phenylboronic acid;

[0074] The electrophilic organic small molecule described in step 1 is 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] (ITIC);

[0075] The volume ratio of 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] to 4-(dimethylamino)phenylboronic acid described in step 1 is 1:1;

[0076] The volume ratio of the total mass of 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] and 4-(dimethylamino)phenylboronic acid to N-methylpyrrolidone described in step 1 is 0.00126 g:1 mL;

[0077] 2. At 60℃ and stirring speed of 300r / min, PolyK 1000% polyetherimide is dissolved in 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinoline dimethane associated molecule solution, and then vacuum degassing is performed to obtain a bubble-free polyetherimide / associated molecule mixed solution;

[0078] The volume ratio of the total mass of the electron-repelling organic small molecule, the electrophilic organic small molecule and the polyetherimide described in step 2 to the organic solvent is 0.16 g:1 mL;

[0079] 3. Pour the bubble-free polyetherimide / associated molecule mixed solution evenly on a clean flat glass plate at a temperature of 70°C, raise the coating knife to a height of 15 μm, scrape horizontally at a speed of 5 cm / s, and then dry to obtain a 10 μm thick and densely structured organic associative molecule / polyetherimide energy storage composite medium film (referred to as IN 1-1);

[0080] The ultrasonic treatment described in step 1 is carried out by using a gradient ultrasonic dispersion treatment combined with a gradient cooling technology, and the specific method is: first, the solution is ultrasonically dispersed for 30 minutes at a power of 200W and a temperature of 30°C, then the power is increased to 400W, the temperature is reduced to 25°C, and the ultrasonic dispersion is carried out for 15 minutes at a power of 400W and a temperature of 25°C, and finally the power is increased to 500W, the temperature is reduced to 20°C, and the ultrasonic dispersion is carried out for 10 minutes at a power of 500W and a temperature of 20°C;

[0081] The vacuum degassing treatment method described in step 2 is to use a gradient vacuum and gradient temperature treatment, specifically: first, stand for 15 minutes in a vacuum environment of 500 mbar and 60°C, then stand for 15 minutes in a vacuum environment of 100 mbar and 65°C, and finally stand for 15 minutes in a vacuum environment of 10 mbar and 70°C;

[0082] The drying method described in step 3 is:

[0083] ①. In an environment without natural light and with a relative humidity of 40%, keep warm at 70℃ for 4 hours and then keep warm at 120℃ for 2 hours;

[0084] ② In an environment without natural light and with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0085] ③. In an environment without natural light and with a relative humidity of 20%, keep warm for 4 hours at 200°C in an argon atmosphere;

[0086] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0087] Example 7: The difference between this example and Example 6 is that the volume ratio of 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] and 4-(dimethylamino)phenylboronic acid described in step 1 is 1:2; the prepared organic associating molecule / polyetherimide energy storage composite dielectric film with a thickness of 10 μm and a dense structure is recorded as IN 1-2. The other steps and parameters are the same as those in Example 1.

[0088] Example 8: The difference between this example and Example 6 is that the volume ratio of 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] and 4-(dimethylamino)phenylboronic acid described in step 1 is 1:3; the prepared organic associating molecule / polyetherimide energy storage composite dielectric film with a thickness of 10 μm and a dense structure is recorded as IN 1-3. The other steps and parameters are the same as those in Example 1.

[0089] Example 9: The difference between this example and Example 6 is that the volume ratio of 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] and 4-(dimethylamino)phenylboronic acid described in step 1 is 2:1; the prepared organic associating molecule / polyetherimide energy storage composite dielectric film with a thickness of 10 μm and a dense structure is recorded as IN 2-1. The other steps and parameters are the same as those in Example 1.

[0090] Example 10: The difference between this example and Example 6 is that the volume ratio of 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] and 4-(dimethylamino)phenylboronic acid described in step 1 is 3:1; the prepared organic associating molecule / polyetherimide energy storage composite dielectric film with a thickness of 10 μm and a dense structure is recorded as IN 3-1. The other steps and parameters are the same as those in Example 1.

[0091] Example 11: A method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associating molecule, which is specifically completed by the following steps:

[0092] 1. Under the conditions of 60° C. and a stirring speed of 300 r / min, the electron-repelling organic small molecules and the electrophilic organic small molecules are dissolved in N-methylpyrrolidone, and then ultrasonically treated for a period of time to obtain an associated molecular solution (PCBM / 4-NB associated molecular solution);

[0093] The electron-repelling organic small molecule described in step 1 is 4-(dimethylamino)phenylboronic acid;

[0094] The electrophilic organic small molecule described in step 1 is 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester (PCBM);

[0095] The volume ratio of 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester to 4-(dimethylamino)phenylboronic acid in step 1 is 1:1;

[0096] The volume ratio of the total mass of 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester and 4-(dimethylamino)phenylboronic acid to N-methylpyrrolidone described in step 1 is 0.00126 g:1 mL;

[0097] 2. At 60℃ and stirring speed of 300r / min, PolyK Ultem 1000% polyetherimide is dissolved in 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinoline dimethane associated molecule solution, and then vacuum degassing is performed to obtain a bubble-free polyetherimide / associated molecule mixed solution;

[0098] The volume ratio of the total mass of the electron-repelling organic small molecule, the electrophilic organic small molecule and the polyetherimide described in step 2 to the organic solvent is 0.16 g:1 mL;

[0099] 3. Pour the bubble-free polyetherimide / associated molecule mixed solution evenly on a clean flat glass plate at a temperature of 70°C, raise the coating knife to a height of 15 μm, scrape horizontally at a speed of 5 cm / s, and then dry to obtain a 10 μm thick and densely structured organic associative molecule / polyetherimide energy storage composite dielectric film (denoted as PN 1-1);

[0100] The ultrasonic treatment described in step 1 is carried out by using a gradient ultrasonic dispersion treatment combined with a gradient cooling technology, and the specific method is: first, the solution is ultrasonically dispersed for 30 minutes at a power of 200W and a temperature of 30°C, then the power is increased to 400W, the temperature is reduced to 25°C, and the ultrasonic dispersion is carried out for 15 minutes at a power of 400W and a temperature of 25°C, and finally the power is increased to 500W, the temperature is reduced to 20°C, and the ultrasonic dispersion is carried out for 10 minutes at a power of 500W and a temperature of 20°C;

[0101] The vacuum degassing treatment method described in step 2 is to use a gradient vacuum and gradient temperature treatment, specifically: first, stand for 15 minutes in a vacuum environment of 500 mbar and 60°C, then stand for 15 minutes in a vacuum environment of 100 mbar and 65°C, and finally stand for 15 minutes in a vacuum environment of 10 mbar and 70°C;

[0102] The drying method described in step 3 is:

[0103] ①. In an environment without natural light and with a relative humidity of 40%, keep warm at 70℃ for 4 hours and then keep warm at 120℃ for 2 hours;

[0104] ② In an environment without natural light and with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0105] ③. In an environment without natural light and with a relative humidity of 20%, keep warm for 4 hours at 200°C in an argon atmosphere;

[0106] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0107] Example 12: This example is different from Example 11 in that the volume ratio of 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester to 4-(dimethylamino)phenylboronic acid in step 1 is 1:2; the prepared 10 μm thick dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as PN1-2. The other steps and parameters are the same as those in Example 1.

[0108] Example 13: The difference between this example and Example 11 is that the volume ratio of 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester to 4-(dimethylamino)phenylboronic acid in step 1 is 1:3; the prepared 10 μm thick dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as PN1-3. The other steps and parameters are the same as those in Example 1.

[0109] Example 14: This example is different from Example 11 in that the volume ratio of 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester to 4-(dimethylamino)phenylboronic acid in step 1 is 2:1; the prepared 10 μm thick dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as PN2-1. The other steps and parameters are the same as those in Example 1.

[0110] Example 15: This example is different from Example 11 in that the volume ratio of 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester to 4-(dimethylamino)phenylboronic acid in step 1 is 3:1; the prepared 10 μm thick dense organic associating molecule / polyetherimide energy storage composite dielectric film is denoted as PN3-1. The other steps and parameters are the same as those in Example 1.

[0111] Comparative Example 1: A method for preparing a pure polyetherimide energy storage dielectric film (PEI dielectric film) is specifically completed by the following steps:

[0112] 1. At 60℃ and stirring speed of 300r / min, PolyK 1000% polyetherimide was completely dissolved in N-methylpyrrolidone, and then vacuum degassing was performed to obtain a bubble-free PEI solution;

[0113] The volume ratio of the polyetherimide mass to N-methylpyrrolidone in step 1 is 0.16 g:1 mL;

[0114] 2. Pour the bubble-free PEI solution evenly onto a clean flat glass plate, raise the coating knife to a height of 15 μm, scrape horizontally at a speed of 5 cm / s, and then dry to form a 10 μm thick and dense PEI dielectric film (referred to as PEI);

[0115] The vacuum degassing treatment method described in step 1 is: the vacuum degassing treatment method adopts gradient vacuum and gradient temperature treatment, specifically: first, stand for 15 minutes in a vacuum environment of 500mbar and 60°C, then stand for 15 minutes in a vacuum environment of 100mbar and 65°C, and finally stand for 15 minutes in a vacuum environment of 10mbar and 70°C;

[0116] The drying method described in step 2 is:

[0117] ①. In an environment without natural light and with a relative humidity of 40%, keep warm at 70℃ for 4 hours and then keep warm at 120℃ for 2 hours;

[0118] ② In an environment without natural light and with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0119] ③. In an environment without natural light and with a relative humidity of 20%, keep warm for 4 hours at 200°C in an argon atmosphere;

[0120] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0121] Comparative Example 2: A method for preparing a polyetherimide energy storage composite dielectric film doped with tetrafluorotetracyanoquinolinedimethane (F4TCNQ / PEI composite dielectric film) is specifically completed in the following steps:

[0122] 1. At 60℃ and stirring speed of 300r / min, PolyK Ultem 1000% polyetherimide and tetrafluorotetracyanoquinodimethane with large electron affinity were completely dissolved in N-methylpyrrolidone, and then vacuum degassing was performed to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0123] In step 1, the volume ratio of tetrafluorotetracyanoquinolinodimethane to polyetherimide is 0.006:1;

[0124] The volume ratio of the total mass of polyetherimide and tetrafluorotetracyanoquinolinodimethane to N-methylpyrrolidone in step 1 is 0.16 g:1 mL;

[0125] 2. Pour the bubble-free F4TCNQ / PEI mixed solution evenly on a clean flat glass plate, raise the coating knife to a height of 15 μm, scrape horizontally at a speed of 5 cm / s, and then dry it to form a 10 μm thick and dense F4TCNQ / PEI composite dielectric film (denoted as F 0.6 );

[0126] The vacuum degassing treatment method described in step 1 is: the vacuum degassing treatment method adopts gradient vacuum and gradient temperature treatment, specifically: first, stand for 15 minutes in a vacuum environment of 500mbar and 60°C, then stand for 15 minutes in a vacuum environment of 100mbar and 65°C, and finally stand for 15 minutes in a vacuum environment of 10mbar and 70°C;

[0127] The drying method described in step 2 is:

[0128] ①. In an environment without natural light and with a relative humidity of 40%, keep warm at 70℃ for 4 hours and then keep warm at 120℃ for 2 hours;

[0129] ② In an environment without natural light and with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0130] ③. In an environment without natural light and with a relative humidity of 20%, keep warm for 4 hours at 200°C in an argon atmosphere;

[0131] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0132] Figure 1 XRD patterns of organic associating molecules / polyetherimide energy storage composite dielectric films prepared in different embodiments;

[0133] Depend on Figure 1 It can be seen that for the F4TCNQ and 4-NB co-doped composite medium, the XRD bun peak of the composite medium shifts slightly to the left as the 4-NB doping content increases, which is attributed to the fact that 4-NB weakens the chain stacking of the PEI molecular chain. However, for the ITIC and 4-NB co-doped composite medium and the PCBM and 4-NB co-doped composite medium, the bun peak of the composite medium did not shift to the left. This may be because F4TCNQ has a small molecular weight and a small electrostatic influence area, which cannot resist the changes in the molecular chain segments caused by 4-NB. The molecular weights of ITIC and PCBM are large, and they form a relatively stable association structure with 4-NB, which reduces the influence of 4-NB on the molecular chain segments.

[0134] Figure 2 Infrared spectra of organic associating molecules / polyetherimide energy storage composite dielectric films prepared in different embodiments;

[0135] Depend on Figure 2It can be seen that the composite medium contains characteristic peaks such as the C=O stretching vibration peak of imide, the CN stretching vibration peak of the imide ring, and the stretching vibration peak of COC, but does not reflect the characteristic peak of the filler. This is mainly due to the low doping content of the filler, which is covered by the strong absorption peak of PEI, and the strong interaction between the molecular association filler leads to the change of the filler characteristic peak.

[0136] Figure 3 1 is a curve diagram of the dielectric constant and dielectric loss of the composite dielectric film at 150°C as a function of frequency, wherein (a) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (b) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; (c) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associating molecules;

[0137] Depend on Figure 3It can be seen that the relative dielectric constant of the F4TCNQ / 4-NB molecular associated filler co-doped composite medium is better than that of pure PEI, and with the increase of F4TCNQ content, the relative dielectric constant of the composite medium increases, which is due to the strong polarity of F4TCNQ. The relative dielectric constants of FN 2-1 and FN 3-1 reach 3.61 and 3.74 at 10Hz, respectively, which are higher than the relative dielectric constants of the composite medium with the same content of F4TCNQ or 4-NB doped alone. This may be due to the interaction between the associated molecules and the PEI molecular chain segments, which increases the dipole moment in the medium and thus improves the polarization ability. In addition, both F4TCNQ and 4-NB have aromatic ring structures, which can interact with the aromatic ring structure in PEI, thereby changing the relative dielectric constant of the PEI composite medium. The relative dielectric constant of the ITIC / 4-NB molecular associated filler co-doped composite medium also increases with the increase of the electron-attracting ITIC molecule content, which can be attributed to the strong dipole-dipole interaction between ITIC and 4-NB, which enhances the overall polarity of the composite medium. In addition, the associated molecules will also affect the stacking of the medium molecular chain, thereby increasing the relative dielectric constant. The influence of PCBM / 4-NB molecular associated filler on the relative dielectric constant of the composite medium is different from that of the other two types. When the PCBM content is high, the relative dielectric constant of the composite medium is improved because its fullerene part has a strong polarization ability and the hollow structure of PCBM can form more interfaces with PEI. However, due to the hollow structure of PCBM, when it forms an associated structure with 4-NB, the influence on the molecular chain segment of the PEI composite medium is relatively complex, so the relative dielectric constant decreases as the proportion of the PCBM content with strong polarity increases.

[0138] The composite media doped with the three types of molecular associated fillers all show excellent dielectric loss characteristics, which are kept within 0.01 in the low frequency range. It can also be seen from the figure that when the PCBM content in the composite medium is high, the dielectric loss will increase slightly. This is mainly because PCBM has a spherical fullerene structure, which is easy to form interfaces and defects in the dielectric body, resulting in a slight increase in dielectric loss. The molecular structures of F4TCNQ and ITIC are approximately planar, so they are more compatible with PEI. The difference in dielectric loss of the three types of composite media at high frequencies is further expanded. This is mainly because polarization charges are more likely to have polarization hysteresis at defects, resulting in increased losses.

[0139] Figure 4: is a Weibull distribution diagram of the breakdown field strength of the composite dielectric film at 150°C; in the figure (a) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (b) is an organic associating molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; (c) is an organic associative molecule / polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with indene-2,1(3H)-dimethylene)]]bis[propylamine] associative molecule; (d) is a pure polyetherimide energy storage composite dielectric film obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associative molecule in Examples 11 to 15; (d) is a polyetherimide energy storage composite dielectric film doped with tetrafluorotetracyanoquinolinodimethane and a polyetherimide energy storage composite dielectric film obtained in Comparative Examples 1 to 2;

[0140] Depend on Figure 4 It can be seen that when the doping ratio of F4TCNQ to 4-NB is 1:1, the breakdown field strength of the composite medium is greatly improved to 671.0kV / mm. When the doping ratio of F4TCNQ to 4-NB is 1:3, the breakdown field strength of the composite medium reaches 660.2kV / mm. The improvement effect of other ratios is poor. This may be because when the ratio of F4TCNQ to 4-NB is 1:1 and 1:3, the interaction force between fillers is strong, and the associated fillers with strong coercive force can withstand the impact of high-energy electrons, and the electrostatic potential distribution between fillers will change, forming a delocalized structure between positive electrostatic potential groups and negative electrostatic potential groups, which can achieve electron capture and scattering, reduce electron energy without causing charge accumulation. When the filler ratio is the other ratios, the interaction between fillers is weak, and the fillers can only play their own capture and scattering roles, and cannot achieve functional synergy.

[0141] When ITIC / 4-NB associative fillers are introduced into PEI, the breakdown field strength of the composite medium can be increased to 704.1 kV / mm when the ratio of ITIC to 4-NB is 1:2. The difference in the improvement ability at different ratios may be due to the difference in the interaction force between the fillers. When PCBM / 4-NB associative fillers are introduced into PEI, the breakdown field strength of the composite medium can be increased to 657.4 kV / mm when the ratio of PCBM to 4-NB is 1:2. The optimal breakdown field strength of the polyetherimide composite medium doped with associative molecular fillers is higher than the breakdown field strength of the pure PEI film, and is also higher than the F4TCNQ single-doped F4TCNQ with a larger electron affinity. 0.6 The film showed good breakdown characteristics. A comprehensive comparison of the characteristic breakdown field strengths of different types of associated fillers and different proportions of content shows that ITIC / 4-NB fillers have the strongest ability to improve the breakdown of composite dielectrics. This may be because ITIC has a longer chain segment and multiple electron-attracting sites. When co-doped with 4-NB, it can form more delocalized structures and has a stronger effect on electron capture and scattering. However, this advantage is not reflected in PCBM / 4-NB.

[0142] Figure 5 The intermolecular force simulation diagram of the associated molecules composed of different types of electrophilic small molecules / electron repelling small molecules according to different proportions in Examples 1 to 15;

[0143] Depend on Figure 5 It can be seen that the interaction energy of the F4TCNQ / 4-NB molecular associated filler reaches the maximum when the filler ratio is 1:1, which is -246.19 kcal / mol. When the filler ratio is 3:1, the interaction energy is the minimum, which is -199.09 kcal / mol. When the interaction energy between fillers is the maximum, the breakdown field strength of the corresponding composite medium is the maximum, and when the interaction energy is the minimum, the breakdown field strength of the corresponding composite medium is the minimum. However, when the content ratio is 1:2, 1:3 and 2:1, the breakdown field strength of the corresponding medium does not increase with the increase of the interaction energy between fillers. The greater the mutual energy of the ITIC / 4-NB molecular associated filler, the greater the breakdown field strength of the corresponding medium, only when the ratio is 2:1 and 1:3, it does not correspond. The breakdown field strength of the PCBM / 4-NB molecular associated filler doped PEI composite medium does not increase with the increase of the intermolecular force. Therefore, the magnitude of the breakdown field strength of the composite medium does not only depend on the intermolecular force of the filler.

[0144] Figure 6 The free volume simulation diagram of the organic associating molecule / polyetherimide energy storage composite dielectric film prepared in Examples 1 to 15;

[0145] Depend on Figure 6It can be seen that when doped with ITIC / 4-NB filler, the free volume of the composite medium is small, all lower than 23.5%. This is mainly because ITIC and 4-NB have strong interaction forces and can form a stable association structure, which reduces the interchain pores. The association formed by ITIC and 4-NB has a large volume and small segment motion, so the motion of the PEI molecular chain is restricted. The interaction energy between F4TCNQ and 4-NB and between PCBM and 4-NB is small, resulting in an unstable molecular association structure and weakening the constraint on the PEI molecular chain segment, thereby increasing the free volume of the composite medium. In addition, the association formed by F4TCNQ and 4-NB has a small molecular weight and is very easy to embed between molecular chains, which increases the pores. The fullerene cage structure of PCBM is also not easy to be tightly stacked, so there is more free volume in the composite medium. The larger the free volume, the easier it is for electrons to accelerate transmission in free space and accumulate energy, which eventually leads to medium breakdown.

[0146] Figure 7 The surface electrostatic potential cloud diagram and potential statistics diagram of the associated molecules. In the figure, (a) is the associated molecule of 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane; (b) is the associated molecule of 4-(dimethylamino)phenylboronic acid / 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1, 2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] associated molecule; (c) is 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associated molecule;

[0147] Depend on Figure 7 It can be seen that ITIC / 4-NB associative fillers have more areas with large electrostatic potential differences, that is, more delocalized spaces, while PCBM / 4-NB and F4TCNQ / 4-NB have relatively fewer areas, which proves that ITIC / 4-NB can effectively capture and scatter carriers, thereby reducing conductivity losses. In addition, after the delocalized structure captures electrons, the electrons can oscillate inside the structure, thereby consuming the energy of the electrons. Even with a long jump distance, the energy of the electrons is relatively low, and the effect on conductivity is small. The above phenomenon shows that the conductive current is not limited to the hopping conduction mechanism. This may also be because hopping conduction ignores the interface effect, and ITIC has a longer molecular chain and can form more interface areas with PEI.

[0148] Figure 8The energy storage density diagram and energy storage efficiency diagram of the composite dielectric film at 150°C are shown in Figures 1 to 5; (a) and (b) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (c) and (d) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; :5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] associating molecules doped with polyetherimide to obtain an organic associating molecule / polyetherimide energy storage composite dielectric film; (e) and (f) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associating molecules in Examples 11 to 15;

[0149] Depend on Figure 8 It can be seen that in the PEI composite medium doped with F4TCNQ / 4-NB associated molecules, when the energy storage efficiency is not less than 90%, the energy storage density of FN 1-1 can reach 5.50 J / cm 3 The corresponding polarization field strength is 600 kV / mm, which is mainly attributed to its good breakdown performance, which increases the maximum polarization electric field. The polarization electric field of FN 1-3 is 580 kV / mm when the energy storage efficiency is 90%, and the energy storage density reaches 4.62 J / cm 3 The polarization electric field of FN 2-1 is only 540 kV / mm when the energy storage efficiency is 91%, but the energy storage density exceeds that of FN 2-1 and can reach 4.70 J / cm 3 This is mainly because the relative dielectric constant of FN 2-1 is greater than that of FN 1-3, and its polarization ability is stronger, so it can achieve higher energy storage performance under lower electric field. The energy storage performance of ITIC / 4-NB associated molecules doped PEI composite medium can reach 6.52J / cm when the content ratio of ITIC and 4-NB is 1:2. 3 , and the energy storage efficiency remains at 91%, the corresponding polarization electric field is 660kV / mm, and the energy storage density is increased by 307.5% relative to PEI. The improvement of the energy storage performance of the PCBM / 4-NB associated molecules on the PEI composite medium is slightly worse than that of F4TCNQ / 4-NB and ITIC / 4-NB. When the ratio of PCBM to 4-NB is 1:1, the energy storage density can reach 5.21J / cm 3, and the energy storage efficiency remains at 94.4%, corresponding to a polarization electric field of 580 kV / mm.

[0150] Fig. 9 The energy storage density diagram and energy storage efficiency diagram of the pure polyetherimide energy storage dielectric film and the polyetherimide energy storage composite dielectric film doped with tetrafluorotetracyanoquinolinodimethane obtained in Comparative Examples 1 to 2 at 150° C.;

[0151] Depend on Fig. 9 It can be seen that the energy storage density of the F4TCNQ / 4-NB associated molecule doped PEI composite medium is increased by 225.6% relative to PEI, the energy storage density of the ITIC / 4-NB associated molecule doped PEI composite medium is increased by 307.5% relative to PEI, and the energy storage density of the PCBM / 4-NB associated molecule doped PEI composite medium is increased by 208.2% relative to PEI, and the energy storage efficiency is also due to PEI. The energy storage density of the PEI composite medium doped with F4TCNQ alone can reach 4.86 J / cm 3, But it is still not as good as the improvement effect of molecular associated fillers.

[0152] Fig.10 Figures 1 and 2 are the hopping conduction fitting diagram and the Schottky barrier fitting diagram of the composite dielectric film. In the figure, (a) and (b) are the organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 1 to 5; (c) and (d) are the organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / tetrafluorotetracyanoquinolinodimethane associating molecules in Examples 6 to 10; (e) and (f) are organic associating molecules / polyetherimide energy storage composite dielectric films obtained by doping polyetherimide with 4-(dimethylamino)phenylboronic acid / 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester associating molecules in Examples 11 to 15.

[0153] Depend on Fig.10It can be seen that the jumping distance of the composite medium is lower than that of PEI, indicating that the electron jumping distance becomes shorter and the conductivity loss will decrease, thus showing better insulation performance. However, a specific analysis found that the jumping distance of the composite medium doped with F4TCNQ / 4-NB filler is 1.29nm when the doping ratio is 1:3, reaching the minimum value. However, the composite medium with the smallest conductance current appears when the doping ratio is 1:1, which does not correspond to its larger jumping distance. In the composite medium doped with IN / 4-NB filler, the conductance current has a smaller conductance current than the other two types, and the jumping distance does not show a corresponding advantage. Analysis of the Schottky barrier fitting data of the composite medium shows that the composite medium has a lower intercept, among which the intercept of the PEI composite medium doped with ITIC / 4-NB molecular association filler is smaller than that of the other two types, and has a higher Schottky barrier, which can effectively hinder carrier injection. This may be because the associated molecules composed of attractive electron fillers and repulsive electron fillers have significant dipole moments, which can form an electric dipole layer at the interface between the electrode and the medium, thereby changing the potential distribution of the interface. ITIC has a longer molecular chain and can form more interfaces, thereby forming a stronger electric dipole layer. As can be seen from the figure, the Schottky barrier of the PCBM / 4-NB molecular associated filler doped PEI composite medium is between the ITIC / 4-NB and F4TCNQ / 4-NB doped composite media, which is consistent with the above hypothesis. Overall analysis shows that the regulation of the conductivity loss of the composite medium by molecular associative fillers is not only affected by the internal hopping transmission, but also the interface injection plays a key role.

[0154] In summary, the organic associating molecule / polyetherimide energy storage composite dielectric film prepared in the present invention has higher high-temperature breakdown field strength, better polarization performance, good energy storage density and more stable high energy storage efficiency.

[0155] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. An organic associating molecule / polyetherimide energy storage composite dielectric film, characterized in that The organic associating molecule / polyetherimide energy storage composite medium film is composed of organic associating molecules and polyetherimide; the organic associating molecules are composed of organic small molecules with electron-repelling properties and organic small molecules with electrophilic properties that are associated through non-covalent bonds; The electron-repelling organic small molecule is 4-(dimethylamino)phenylboronic acid; The electrophilic organic small molecule is tetrafluorotetracyanoquinolinodimethane, 2,2'-[[[6,6,12,12-tetrakis(4-hexylphenyl)-6,12-dihydrodithio[2,3-D:2',3'-D']-S-indolol[1,2-B:5,6-B']dithiophene-2,8-diyl]bis[methylene(3-oxo-1H-indene-2,1(3H)-dimethylene)]]bis[propylamine] or 2ALPHA-phenyl-1,2(2ALPHA)-homo[5,6]fullerene-C60-LH-2ALPHA-butyric acid methyl ester.

2. The organic associating molecule / polyetherimide energy storage composite dielectric film according to claim 1, characterized in that The volume ratio of the organic associating molecule to the polyetherimide is 0.007:

1.

3. The organic associating molecule / polyetherimide energy storage composite dielectric film according to claim 1, characterized in that The volume ratio of the electrophilic organic small molecules to the electron-repelling organic small molecules is 1:(0.3-3).

4. The method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film according to claim 1, characterized in that The preparation method is specifically completed according to the following steps:

1. dissolving the electron-repelling organic small molecules and the electrophilic organic small molecules in an organic solvent, and then ultrasonically treating for a period of time to obtain an associated molecular solution; 2. dissolving polyetherimide into the associating molecule solution, and then performing vacuum defoaming treatment to obtain a bubble-free polyetherimide / associating molecule mixed solution; 3. Scrape the bubble-free polyetherimide / associated molecule mixed solution on the substrate, and then dry it to obtain an organic associative molecule / polyetherimide energy storage composite medium film.

5. The method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film according to claim 4, characterized in that The organic solvent described in step one is N-methylpyrrolidone, dimethylacetamide or N,N-dimethylformamide; the volume ratio of the total mass of the electron-repelling organic small molecules and the electrophilic organic small molecules described in step one to the organic solvent is (0.00105g~0.00126g):1mL; the volume ratio of the total mass of the electron-repelling organic small molecules, the electrophilic organic small molecules and the polyetherimide described in step two to the organic solvent is (0.15g~0.18g):1mL.

6. The method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film according to claim 4, characterized in that In step 1, under the conditions of 60°C to 70°C and a stirring speed of 300r / min to 500r / min, the electron-repelling organic small molecules and the electrophilic organic small molecules are dissolved in an organic solvent; the ultrasonic treatment described in step 1 is carried out by using a gradient ultrasonic dispersion treatment combined with a gradient cooling technology, and the specific method is: first, the solution is ultrasonically dispersed for 30 minutes at a power of 200W and a temperature of 30°C, then the power is increased to 400W, the temperature is reduced to 25°C, and the solution is ultrasonically dispersed for 15 minutes at a power of 400W and a temperature of 25°C, and finally the power is increased to 500W, the temperature is reduced to 20°C, and the solution is ultrasonically dispersed for 10 minutes at a power of 500W and a temperature of 20°C.

7. The method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film according to claim 4, characterized in that In step 2, polyetherimide is dissolved in the associated molecular solution at 60°C to 70°C and a stirring speed of 300r / min to 500r / min; the vacuum defoaming treatment method described in step 2 adopts gradient vacuum and gradient temperature treatment, specifically: first, let it stand for 5min to 15min in a vacuum environment of 500mbar and 60°C, then let it stand for 5min to 15min in a vacuum environment of 100mbar and 65°C, and finally let it stand for 5min to 15min in a vacuum environment of 10mbar and 70°C.

8. The method for preparing an organic associating molecule / polyetherimide energy storage composite dielectric film according to claim 4, characterized in that The drying method described in step 3 is: ①. In an environment without natural light and with a relative humidity of 40%, keep warm at 70℃ for 4 hours and then keep warm at 120℃ for 2 hours; ② In an environment without natural light and with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours; ③. In an environment without natural light and with a relative humidity of 20%, keep warm for 4 hours at 200°C in an argon atmosphere; ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction; The thickness of the organic associated molecule / polyetherimide energy storage composite medium film described in step three is 3 μm to 15 μm.

9. The use of an organic associating molecule / polyetherimide energy storage composite dielectric film as claimed in claim 1, characterized in that An organic associative molecule / polyetherimide energy storage composite dielectric film is used as an energy storage material for a pulse capacitor; the pulse capacitor is used in the field of electric-thermal field coupling of new energy vehicle inverters, electromagnetic emission pulse systems or aerospace exploration energy storage systems.

10. The use of an organic associating molecule / polyetherimide energy storage composite dielectric film as claimed in claim 1, characterized in that An organic associative molecule / polyetherimide energy storage composite dielectric film is used in a pulse energy storage device under electrothermal field coupling conditions. The pulse energy storage device can achieve an energy storage density of 6.52 J / cm at 150°C, 660 kV / mm, and a charge and discharge efficiency of 91%. 3 .

Citation Information

Patent Citations

  • Preparation method of fullerene modified polyetherimide polymer material

    CN111978573A

  • High-temperature-resistant composite dielectric and preparation method and application thereof

    CN116791277A

  • Polyetherimide-based energy storage composite dielectric film and preparation method and application thereof

    CN117683350A

  • Preparation method of polyetherimide composite material film for improving capacitive energy storage density

    CN118459807A